Базові засади формування потенціалу фінансово-економічної стійкості соціально-економічних систем - Куцик, П. О.; Герега, О. В. (Видавництво Львівської політехніки, 2015)
Систематизовано й узагальнено наявні базові засади формування, виміру та управління потенціалом фінансово-економічної стійкості суб’єктів вітчизняної економіки. Наведено результати критичного аналізу використовуваного в теорії і практиці інструментарію встановлення рівня фінансово-економічної стійкості підприємства, його використання в управлінні. Сформульовано окремі аспекти розвитку базових засад управління процесами формування фінансово-економічної стійкості економічних систем. In Article the basic principles of formation, measurement and management of potential financial and economic stability of the domestic economy subjects were systematic and generalized. The results of the critical analysis used in the theory and practice tools for setting the financial and economic viability, and its use in the processes of management were shown. The certain aspects of the basic principles of management processes of formation the financial and economic stability for economic systems were formulated. There are a number of arguments that the potential financial and economic stability of market modern economy is the key criteria for their ability to adapt to the dynamism of global socio-economic environment. The adaptive to the conditions of the national economy concept of management tools and adequate capacity building process control of financial and economic stability of economic entities of the national economy providing the possibility of overcoming the crisis, gaining their investment attractiveness and improve conditions for transition to the innovative type of development were proved. As a result of the critical analysis set out in theoretical research field of functional evaluative and analytical instruments concluded its discrepancy practical needs effective management processes forming potential of domestic enterprises. Proved that the potential financial and economic stability of current social and economic systems objectively considered adequate due to their specific structure and terms of economic resources, the effectiveness of management practices regarding the dynamic transformation of these resources, and the result is reflected in the market position of the economic system, the value of its equity. In this context the necessity to develop adequate national practice patterns of absolute figures, their normative values and approaches to handling their dynamics. Formulated the basic principles of forming potential of the company, among which highlighted the urgency to implement in domestic enterprises monitoring and diagnostic systems for the purpose of identifying changes in the external and internal environment of the principles for assessment and analysis of potential stability, prerequisites correction parameters capacity in management decisions aimed effective processes to ensure capacity building of sustainable enterprise development.
Basic principles of forming the financial and economic sustainability potential of socio-economic systems
Keywords: економічні ресурси; потенціал; фінансово-економічна стійкість; повна діаграма деформування бетону; управління; економічний інструментарій; economic resources; potential; financial and economic stability; the continuity equation of deformation; governance; economic tools